The Humanitarian-Development-Peace nexus: Towards differentiated configurations - Sebastian Weishaupt (United Nations Research Institute for Social Development (UNRISD), 2020)
This paper examines and problematizes recent conceptualizations of the HumanitarianDevelopment-Peace (HDP) nexus, which has been proposed as a comprehensive response to protracted crises and, in particular, protracted displacement. It is based on a literature review and primarily addresses those organizations currently experimenting with the idea of nexus programming. The paper aims to encourage a more differentiated debate about the HDP nexus. For that purpose, four aspects that deserve further inquiry are fleshed out and tentatively sketched as determinants for a variety of potential nexus configurations. First, the common conceptualization of humanitarian aid, development and peace as sectoral silos is problematized as it emphasizes separations and disregards overlaps. Attention is drawn to ideological differences within each of the three sectors, as they illustrate that differences between and overlaps of humanitarian, development and peace objectives, activities and outcomes are organization specific. Second, inter- and intraorganizational perspectives on the HDP nexus are distinguished, as they provide starting points for bridging and/or breaking the silos. Third, the disregard of contextual particularities in conceptualizing the nexus is problematized, calling for further exploration regarding the conditions that enable or prevent a nexus approach in a specific context. Fourth, and related to the former, it is argued that the substance of nexus configurations needs to become a more prominent element in the debate. Answers need to be found not only for how the HDP nexus can be pursued, facilitated and institutionalized but with which activities and outcomes it can be substantiated. In conclusion, the paper acknowledges the potential of the HDP nexus to encourage thinking beyond distinct spheres of competence and intervention but warns against the conceptualization and proliferation of a nexus-blueprint.
Keywords: 330; Triple nexus; protracted crises; protracted displacement; silos